Amnion Epithelial Cells of Buffalo (Bubalus Bubalis) Term Placenta Expressed Embryonic Stem Cells Markers and Differentiated into Cells of Neurogenic Lineage In Vitro. Issue 1 (2nd January 2016) - Ghosh, K.; Selokar, N. L.; Gahlawat, S. K.; Kumar, Dharmendra; Kumar, Pawan; Yadav, P. S.
ABSTRACT: Aim of the present study was the isolation, culture, and characterization of amniotic membrane-derived epithelial cells (AE) from term placenta collected postpartum in buffalo. We found that cultured cells were of polygonal in shape, resistance to trypsin digestion and expressed cytokeratin-18 indicating that they were of epithelial origin. These cells have negative expression of mesenchymal stem cell markers (CD29, CD44, and CD105) and positive for pluripotency marker (OCT4) genes indicated that cultured cells were not contaminated with mesenchymal stem cells. Immunofluorescence staining with pluripotent stem cell surface markers, SSEA-1, SSEA-4, TRA-1-60, and TRA-1-81 indicated that these cells may retain pluripotent stem cell characteristics even after long period of differentiation. Differentiation potential of these cells was determined by their potential to differentiate into cells of neurogenic lineages using retinoic acid. In conclusion, we demonstrate that AE cells expressed pluripotent stem cell markers and have propensity to differentiate into cells of neurogenic lineage upon directed differentiation in vitro .